2019
DOI: 10.1093/tbm/ibz178
|View full text |Cite
|
Sign up to set email alerts
|

A case study of a theory-based method for identifying and reporting core functions and forms of evidence-based interventions

Abstract: Adaptation of existing evidence-based interventions (EBIs) to improve their fit in new contexts is common. A critical first step in adaptation is to identify core functions (purposes) and forms (activities) of EBIs. Core functions should not be adapted as they are what account for the efficacy of EBIs. Despite their importance, core functions are rarely identified by EBI developers; methods for identifying them post hoc are lacking. We present a case study of theory-based methods for identifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 33 publications
0
55
0
Order By: Relevance
“…To date, evidence is inconclusive regarding whether adaptations have a positive, negative or neutral effect on intervention outcomes (Breitenstein et al, 2010 ). With this in mind, more recently, it is suggested that achieving an appropriate balance between fidelity and adaptation is needed and that in certain circumstances adaptation may in fact be a critical element of a behaviour change intervention (Hawe, Shiell, & Riley, 2004 ; Holliday et al, 2009 ; Kirk et al, 2019 ; McHugh et al, 2009 ). However, despite the clear need for careful and explicit consideration of intervention adaptation and what is considered ‘appropriate’ or desirable, several systematic reviews have shown that this particular aspect remains an under-addressed area of health behaviour change intervention research (Durlak & DuPre, 2008 ; Yamato, Maher, Saragiotto, Hoffmann, & Moseley, 2016 ; Yu, Balasubramanaiam, Offringa, & Kelly, 2018 ).…”
Section: Issues With Intervention Fidelity – What Is Not Being Done and When It Is Being Done What Is Lacking?mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, evidence is inconclusive regarding whether adaptations have a positive, negative or neutral effect on intervention outcomes (Breitenstein et al, 2010 ). With this in mind, more recently, it is suggested that achieving an appropriate balance between fidelity and adaptation is needed and that in certain circumstances adaptation may in fact be a critical element of a behaviour change intervention (Hawe, Shiell, & Riley, 2004 ; Holliday et al, 2009 ; Kirk et al, 2019 ; McHugh et al, 2009 ). However, despite the clear need for careful and explicit consideration of intervention adaptation and what is considered ‘appropriate’ or desirable, several systematic reviews have shown that this particular aspect remains an under-addressed area of health behaviour change intervention research (Durlak & DuPre, 2008 ; Yamato, Maher, Saragiotto, Hoffmann, & Moseley, 2016 ; Yu, Balasubramanaiam, Offringa, & Kelly, 2018 ).…”
Section: Issues With Intervention Fidelity – What Is Not Being Done and When It Is Being Done What Is Lacking?mentioning
confidence: 99%
“…a video or booklet), or the operationalisation of a behaviour change technique (BCT) to be adapted, as long as it retains fidelity to the underlying intervention theory (Keogh, Matthews, & Hurley, 2018 ) or the ‘function’ of the component or BCT (e.g. to ‘provide instruction on how to perform the behaviour’) (Hawe, Shiell, & Riley, 2004 ; Hawe, Shiell, Riley, & Gold, 2004 ; Kirk et al, 2019 ; McHugh et al, 2009 ). Clear specification of the intervention components and hypothesised mechanisms of change using logic models and taxonomies such as the BCT Taxonomy v1 (Michie et al, 2013 ) is therefore essential to facilitate this.…”
Section: Issues With Intervention Fidelity – What Is Not Being Done and When It Is Being Done What Is Lacking?mentioning
confidence: 99%
“…Historically, deviation from the research protocol was perceived as a threat to implementation fidelity, compromising the effectiveness of the intervention (Bopp et al, 2013;Chambers and Norton, 2016). However, recent literature recognises that although the underlying principles that make the intervention effective require perfect fidelity (core functions), the tailoring of strategies which support each intervention principle (forms) is necessary to improve context fit (Kirk et al, 2019;Perez Jolles et al, 2019). Although identifying these core functions and forms strengthen local implementation, these components are rarely specified by intervention developers (Kirk et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Core functions and forms can also be identified post hoc. 28 The idea of making causal pathways explicit is also reflected in PCORI’s methodology standards for studies of complex interventions. 22 In the case studies below, we discuss the importance of delineating function versus form.…”
Section: Discussionmentioning
confidence: 99%